THE IMPACT OF THE VIRTUAL LABORATORY ON THE PHYSICS LEARNING PROCESS - Juškaite, Loreta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
ICT has invaded the educational process and is providing us with many opportunities to exploit. An additional challenge faced by Physic educators has been the integration of Virtual laboratories in the teaching process. In recent years, Inquiry-Based Science Education has proved its efficacy in education by expanding on “traditional” lessons and motivating students to actively participate in science. Digital technologies support necessary educational innovations and can be the catalyst for change in educational patterns (in regard to its form, space, functions, services, tools, roles, procedures). Virtual laboratories are an essential digital tool. In fact, many Latvian schools are equipped with computer classes, tablets and high-speed internet connection while using a huge variety of web-based learning applications, simulations and visualizations. The paper evaluates necessary skills and abilities which can be developed at the secondary level, analysing and planning the interaction between the physics education process and technological development. The article also highlights the direction of future research. The paper evaluates necessary skills and abilities which can be developed at the secondary level, analysing and planning the interaction between the physics education process and technological development. The article also highlights the direction of future research